Investigation of a gain-switched laser pumped by an acousto-optic -switched Ho : YAG laser. (September 2016) - Yuan, Jin-He; Chen, Yi; Yang, Hong-Yu; Yao, Bao-Quan; Duan, Xiao-Ming; Dai, Tong-Yu; Ju, You-Lun
Abstract: We demonstrate a gain-switched laser pumped by a high energy Ho : YAG laser. The maximum output power of in the spectrum range from to is obtained at a pulse repetition rate of, corresponding to a pulse energy of . With a volume Bragg grating (VBG) for compressing the linewidth, a output power with a narrow linewidth is obtained at . The pulse shapes obtained at different pump energies are also studied and analysed. A minimum pulse width of is achieved at a pump energy of, corresponding to a peak power of .